Spatiotemporal evolution of the early Permian multi-source-to-sink system in the northwestern margin of the North China Block: Implications for the paleogeographic reconstruction along the southern margin of the Paleo-Asian Ocean - Wang, Zhiwei; Liu, Lei; Hu, Jianling; Li, Dan; Chen, Hongde; Zhu, Shuyue; Zhang, Chenggong; Zhao, Junxing (Palaeogeography, palaeoclimatology, palaeoecology, 2024)
The northwestern margin of the North China Block, situated at the intersection of multiple tectonic units, presents a complex geological setting that challenges paleogeographic reconstructions. The subduction and closure of the Paleo-Asian Ocean have further complicated the understanding of sediment provenance during the Early Permian. In this study, we integrated sedimentological, geochemical, and UPb dating methods to delineate the Early Permian source-to-sink systems along the northwestern margin of the North China Block. The identification of four key source-to-sink systems—the Alxa, Langshan, Serteng–Wula, and Jining–Daqing—reveals a pronounced east–west provenance differentiation, indicative of the regional tectonic and sedimentary responses to subduction of the Paleo-Asian Ocean. During the Shanxi Formation deposition, the western regions were dominated by the Inner Mongolian continental island arc as a principal sediment source, fostering distal meandering river deltas. Conversely, the eastern regions were predominantly influenced by the North China Block basement, leading to the deposition of proximal, shallow meandering river deltas. As the Shihezi Formation deposition ensued, the western source-to-sink systems continued to receive sediments from the uplifted Inner Mongolian Arc, transitioning to distal braided river deltas amidst an orogenic setting. Meanwhile, the eastern systems, particularly Jining–Daqing, showed increased contributions from the North China Block basement, forming mixed-source, shallow braided river deltas. This research provides a refined understanding of the spatiotemporal evolution of source-to-sink systems and their responses to the tectonic setting, offering valuable insights into the paleogeographic evolution along the southern margin of the Paleo-Asian Ocean. •Source-to-sink methods were used to reconstruct the paleogeography of the Permian North China Block.•The western and eastern parts of the margin had different sources and settings.•The Permian closure of the Paleo-Asian Ocean was not a simple west–east process.•Four main source-to-sink systems were identified from west to east: Alxa, Langshan, Serteng-Wula, and Jining-Daqing.